Impact of Mass and Lattice Difference on Thermal Boundary Conductance. Issue 1779 (2015) - Choi, Changjin; Roberts, Nick
ABSTRACT: The impact of mass and lattice difference on thermal boundary conductance is investigated using non-equilibrium molecular dynamics with the Lennard-Jones interatomic potential. Results show that the maximum thermal boundary conductance is achieved when the mass and the lattice of two dissimilar materials are matched, although the composite thermal conductance is not necessarily a maximum. It is observed that the small difference in mass and potential well depth has as significant an impact as large differences, and that the frequency mismatch is an important factor that affects thermal boundary conductance. It is, also, found that inelastic scattering begins to play a role at the interface as the temperature increases.